#TITLE_ALTERNATIVE# - MULYANI, SRI
The existing of heteroatom on conjugation hydrocarbon compound couses the value of Coulomb integral and resonance integral for every atom are no longer the same. These changes are stated in parameter h and k, which are corresponding to Coulomb integral and resonance integral in standard ß0 units. Using semiempirical LCAO-MO method like HMO, the calculation of energy and the wave functions of orbital molecule of nitrogen heterocyclic compound i.e. pyridine has been performed, providing the variation of the value of h between 0.1-1.0 and k between 0.4-1.1. The result then used to calculate physical units such as dipole moment, ionization potential, resonance energy and heat combustion. Compare to experimental data indicates that there are relation between parameter h and k. In other word that for every h value has appropriate k value. Calculation based on both dipole moment and ionization potential gives h = 0,4 and k = 0,75. Application of this h and k values on o-phenantroline gives dipole moment and ionization potential of 3,95 D and 8,25 eV respectively.